PENGARUH LATIHAN DEPTH JUMP TERHADAP POWER OTOT TUNGKAI SAAT MELAKUKAN SPIKE PADA TIM BOLA VOLI PUTRA PENDIDIKAN OLAHRAGA UNIVERSITAS RIAU - Marunduri, Yogi Wijaya; Juita, Ardiah; ', Ramadi (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2016)
Abstract : The problem of this research is the lack of leg muscles power of male volleyball team in physical education department. Because there is lack of power leg muscles when doing spike in volleyball. It can be seen on how slow the force from the leg right before jumping, that when the player hit the ball up in the air, it can be reached or blocked by the opponent easily. Moreover, many balls stuck in the net because of the lack of force from the leg. This is an experimental research to see the impact of the training. And the purpose of this research is to see the impact of 16 times depth jump training to the power of leg muscleswhile doing spike in Male Volleyball team, Physical Education Department, Riau University. The population in this research is a team of 12 male volleyball players in Physical Education Department, Riau University. The sampling method that was used is total sampling method, where we took the total population as a sample. The data was collected from a pre-test and post-test session. We used a vertical jump test as the instrument for this research to measure the power of leg muscles, and then analyzed the data using T-test method. According to the result of data reviews and analysis, it can be concluded that there is an impact of 16 depth jump training to the power of leg muscles while doing spike in Male Volleyball team, Physical Education Department, Riau University. It shows that Tvalue= 5,91 and Ttable = 1,796 ; which means that Tvalue>Ttable; at Î±=0.05.Keywords :Depth Jump, Power, Leg Muscles, Volleyball.